Harvesting the biosphere : what we have taken from nature - Smil, Vaclav (MIT Press, 2013)
The biosphere - the Earth's thin layer of life - dates from nearly four billion years ago, when the first simple organisms appeared. Many species have exerted enormous influence on the biosphere's character and productivity, but none has transformed the Earth in so many ways and on such a scale as Homo sapiens. In this book, the author offers an interdisciplinary and quantitative account of human claims on the biosphere's stores of living matter, from prehistory to the twenty-first century. The author examines all harvests - from prehistoric man's hunting of megafauna to modern crop production - and all uses of harvested biomass, including energy, food, and raw materials. Without harvesting of the biomass, the author points out, there would be no story of human evolution and advancing civilization; but at the same time, the increasing extent and intensity of contemporary biomass harvests are changing the very foundations of civilization's well-being. In this detailed and comprehensive account, the author presents the best possible quantifications of past and current global losses in order to assess the evolution and extent of biomass harvests. Drawing on work in disciplines ranging from anthropology to environmental science, this book offers a long-term, planet-wide perspective on human-caused environmental change. -- Jacket.